ILC2 Cells Promote Th2 Cell Differentiation in AECOPD Through Activated Notch-GATA3 Signaling Pathway - Jiang, Min; Cai, Ren; Wang, Jing; Li, Zheng; Xu, Dan; Jing, Jing; Zhang, Fengbo; Li, Fengsen; Ding, Jianbing (Frontiers in Immunology, 2021)
This study is to investigate the capacity of type 2 innate lymphoid cells (ILC2s) in regulating the Th2 type adaptive immune response of acute exacerbation of chronic obstructive pulmonary disease (AECOPD). The study enrolled healthy people, stable chronic obstructive pulmonary disease (COPD) patients, and AECOPD patients. Flow cytometry was used to detect Th2 and ILC2 cells in the peripheral blood. In addition, ILC2s from the peripheral blood of AECOPD patients were stimulated with PBS, IL-33, Jagged1, DAPT, IL-33+Jagged1, IL-33+DAPT, and IL-33+Jagged-1+DAP in vitro. The levels of cytokines in the culture supernatant were detected by ELISA and the culture supernatant was used to culture CD4 + T cells. The mRNA and protein levels of Notch1, hes1, GATA3, RORα, and NF-κB of ILC2s were detected by real-time PCR and Western blot. The proportion of Th2 and ILC2s was significantly increased in the peripheral blood of AECOPD patients, alone with the increased Notch1, hes1, and GATA3 mRNA levels. In vitro results showed that the mRNA and protein levels of Notch1, hes1, GATA3 and NF-κB were significantly increased after stimulation with Notch agonist, meanwhile, the level of type 2 cytokines were increased in the supernatant of cells stimulated with Notch agonist, and significantly promoted differentiation of Th2 cells in vitro. Disruption of Notch pathway weakened GATA3 expression and cytokine production, and ultimately affected the differentiation of Th2 cells. In conclusion, our results suggest that ILC2s can promote Th2 cell differentiation in AECOPD via activated Notch-GATA3 signal pathway.